PENERAPAN PSIKOLOGI PADA MADRASAH DAN PONDOK PESANTREN - Mukhlishi, Mukhlishi (Universitas Islam Madura, 2017)
Theories application of educational psychology and its influence on the learning process. Based on this understanding, leaders of educational institutions schools are expected to analyze the educational problems of educational psychology perspective, able to scrutinize the actual issues in educational psychology and is able to contribute conceptual problem solving in educational practice educational psychology perspective. Pesantren are now able to respond to changing times (khalaf) has added value because of the completeness of education in various disciplines of science. It must be responded to many people untuknpesantren leaders assess that the education system should be able to last for delivering the nation achieve development goals in education, which is integral human development.